adhesive material

JP7600543B2Active Publication Date: 2024-12-17AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020089644
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-22
Publication Date
2024-12-17
Estimated Expiration
2040-05-22

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、透湿性及び耐水性に優れる貼付材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600543000008
    Figure 0007600543000008
  • Figure 0007600543000001
    Figure 0007600543000001
  • Figure 0007600543000002
    Figure 0007600543000002
Patent Text Reader

Abstract

To provide an adhesive material that is superior in moisture permeability and water resistance.SOLUTION: An adhesive material includes: a support having the moisture permeability of 2,000 g / (m2 / day) or more; and an adhesive layer having the moisture permeability of 2, 500 g / (m2 / day) or more. In the adhesive material, the adhesive layer comprises a polymer having a constitutional unit based on a monomer having a (meth) acryloyl oxy group, urethane bond and linear polyoxyalkylene chain, the polyoxyalkylene chain has a number-average molecular weight of 1,000 or more, and the content of an ethylene oxide unit is 50 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a patch. [Background technology]

[0002] Patches to be applied to the skin are required to have excellent moisture permeability so that moisture generated by sweat from the skin can evaporate to the outside of the patch, and are also required to have excellent water resistance so that they do not peel off due to sweat or showering.

[0003] Patent Document 1 states that the moisture permeability is 3,000 g / (m 2 ·day) or more and a moisture permeability of 5,000g / (m 2 The adhesive layer comprises a polyurethane-based adhesive obtained by reacting (1) an active hydrogen compound containing a polyoxyalkylene structure having a number average molecular weight of 5,000 or more and an average functionality of 2 or more, (2) an active hydrogen compound containing a polyoxyalkylene structure having a number average molecular weight of 1,500 to 5,000 and an average functionality of 1, and (3) an organic polyisocyanate. The average functionality of all active hydrogen compounds used to obtain the adhesive is 2 to 2.6, and the content of ethylene oxide units of all active hydrogen compounds in the adhesive is 3 to 8 wt%.

[0004] Furthermore, Patent Document 1 discloses that moisture permeability can be improved by increasing the proportion of ethylene oxide units in the pressure-sensitive adhesive layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5457446 Summary of the Invention [Problem to be solved by the invention]

[0006] The moisture permeability of the patch described in Patent Document 1 is insufficient. Therefore, in order to improve the moisture permeability of the patch, the inventors of the present application investigated increasing the ethylene oxide units in the polymer contained in the adhesive layer constituting the patch described in Patent Document 1. As a result, it was found that although the moisture permeability of the patch was improved, the water resistance was insufficient. The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an adhesive material that is excellent in moisture permeability and water resistance. [Means for solving the problem]

[0007] The present invention includes the following [1] to [9]. [1] Moisture permeability is 2,000g / (m 2 ·day) or more and a moisture permeability of 2,500g / (m 2 a polymer having a structural unit based on a monomer having a (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain, the polyoxyalkylene chain having a number average molecular weight of 1,000 or more and an ethylene oxide unit content of 50 mass% or less. The monomer includes a monomer a having one (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain in one molecule, and the proportion of the monomer a to the total mass of the monomers is 70 to 100 mass %. A patch. [2] The pressure-sensitive adhesive layer is located on at least a part of the surface of the support, and the moisture permeability of the area where the support and the pressure-sensitive adhesive layer overlap is 2,000 g / (m 2 The patch described in [1], wherein the duration is 1-days or more. [3] The patch according to [1] or [2], wherein the pressure-sensitive adhesive layer has a thickness of 10 to 40 μm. [4] The patch according to any one of [1] to [3], wherein the support is a film, a porous film, a woven fabric or a nonwoven fabric, and the material of the support is at least one selected from an ether-based urethane resin, an ester-based urethane resin, a polyester resin, a polyamide resin and a polyolefin resin. [5] The patch according to any one of [1] to [4], further comprising a carrier in a peelable state on the side of the pressure-sensitive adhesive layer opposite to the side on which the support is provided. [6] The patch described in any one of [1] to [5], which has an adhesive strength to human skin of 0.1 to 1.2 N / 15 mm. [7] The patch described in any one of [1] to [6], which is for medical use. [8] The patch described in [7], which is a dressing material. [9] The patch described in any one of [1] to [8], which is a patch to be applied directly to the skin. Effect of the Invention

[0008] According to the present invention, a patch having excellent moisture permeability and water resistance can be provided. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view showing one embodiment of a patch according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The terms used in this specification are defined as follows. A numerical range expressed by "to" means that the numerical values ​​before and after the "to" are the lower and upper limits of the numerical range. "Unit" means the grouping of atoms formed directly by polymerization of a monomer. "(Meth)acryloyloxy" means either or both of acryloyloxy and methacryloyloxy. The term "number of functional groups" means the number of (meth)acryloyloxy groups in one molecule, unless otherwise specified. The term "average number of functional groups" refers to the average number of (meth)acryloyloxy groups per formula weight or per molecule, with the number average molecular weight being one unit, obtained based on a chemical formula, unless otherwise specified.

[0011] The number average molecular weight (hereinafter also referred to as "Mn") is the polystyrene-equivalent molecular weight obtained by measuring with gel permeation chromatography (GPC) using a calibration curve prepared using standard polystyrene samples of known molecular weight. The molecular weight distribution is the value obtained by dividing the mass average molecular weight (hereinafter also referred to as "Mw"; the polystyrene-equivalent molecular weight obtained by GPC like Mn) by Mn (hereinafter also referred to as "Mw / Mn"). Note that in the GPC measurement, if a peak of unreacted low molecular weight components (monomers, etc.) appears, the peak is excluded to obtain Mn. Even if Mn is specified, if Mw / Mn does not exist, the molecular weight represented by the formula weight obtained based on the chemical formula shall be substituted.

[0012] The hydroxyl value of a compound having one hydroxyl group and a linear polyoxyalkylene chain, or a compound having two hydroxyl groups and a linear polyoxyalkylene chain, described below, is a value obtained by measurement in accordance with JIS K1557 (2007 edition). The hydroxyl group-equivalent molecular weight is a value calculated by applying the hydroxyl value to the formula "56100 / (hydroxyl value)×(number of hydroxyl groups in the initiator)".

[0013] The patch of this embodiment has a moisture permeability of 2,000 g / (m 2 ·day) or more and a moisture permeability of 2,500g / (m 2 The adhesive layer is provided for at least 1.5 days. The pressure-sensitive adhesive layer of this embodiment contains a polymer (hereinafter referred to as "polymer A") having a constituent unit based on a monomer (hereinafter referred to as "monomer x") having a (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain. The polyoxyalkylene chain has a number average molecular weight of 1,000 or more and an ethylene oxide unit content of 50 mass% or less.

[0014] <monomer x> Monomer x is a monomer having a (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain. The monomer x constituting the polymer may be of two or more types. The number of (meth)acryloyloxy groups in the monomer x is preferably 1 to 4, more preferably 1 or 2, and even more preferably 1, from the viewpoint of flexibility of the resulting polymer. The number of urethane bonds in the monomer x is preferably 1 to 4, more preferably 1 or 2, and even more preferably 1, since the viscosity of the curable composition containing the monomer x becomes low.

[0015] The proportion of (meth)acryloyloxy groups to the total amount of monomer x is preferably 0.15 to 7.0 mass%, more preferably 0.2 to 2.3 mass%, and even more preferably 0.22 to 1.7 mass%, from the viewpoints of the curability of the curable composition containing monomer x and the flexibility of the resulting polymer. The ratio of the urethane bond to the total amount of the monomer x is preferably 0.15 to 1.6 mass%, more preferably 0.18 to 2.2 mass%, and even more preferably 0.20 to 1.4 mass%, from the viewpoints of the curability of the curable composition containing the monomer x and the flexibility of the resulting polymer.

[0016] The ratio of urethane bonds to the total amount of monomer x is calculated from the following formula, assuming that all of the isocyanate groups in the compound used to produce monomer x form urethane bonds (molecular weight 59). Urethane bond content (unit: mass%) = Mi x 59 / Wb x 100 Wb: total mass of monomer x Mi: Total number of moles of isocyanate groups present in the compound used to produce monomer x of mass Wb

[0017] The Mn of the polyoxyalkylene chain in the monomer x is 1,000 or more, and from the viewpoint of the flexibility and adhesiveness of the resulting polymer, it is preferably from 1,000 to 25,000, more preferably from 3,000 to 24,500, and even more preferably from 4,000 to 24,000. The Mw / Mn of the polyoxyalkylene chain in the monomer x is preferably from 1.03 to 1.2, more preferably from 1.04 to 1.15, and even more preferably from 1.05 to 1.14, since the viscosity of the curable composition containing the monomer x becomes low.

[0018] The content of ethylene oxide units in the polyoxyalkylene chain in the monomer x is 0 to 50% by mass, preferably 0 to 40% by mass, and more preferably 0 to 25% by mass. When the content of ethylene oxide units is equal to or less than the upper limit, the water resistance of the patch having an adhesive layer containing a polymer having a structural unit based on the monomer x is improved. The ethylene oxide content of the monomer x is 1 It can be calculated by H-NMR.

[0019] The content of the propylene oxide unit in the polyoxyalkylene chain in the monomer x is preferably from 50 to 100% by mass, more preferably from 60 to 100% by mass, and further preferably from 75 to 100% by mass.

[0020] The Mn of the monomer x is preferably 1,000 to 35,000, more preferably 6,000 to 30,000, and further preferably 7,000 to 25,000. When the Mn of the monomer x is within the above range, the viscosity of the curable composition containing the monomer x is easily adjusted, and the adhesiveness of the obtained polymer is easily improved. The Mw / Mn of the monomer x is preferably from 1.01 to 1.30, more preferably from 1.03 to 1.20, further preferably from 1.04 to 1.15, and particularly preferably from 1.05 to 1.14.

[0021] The monomer x preferably contains one or both of the following monomer a and monomer b. Monomer a: a monomer having one (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain in one molecule. Monomer b: A monomer having two (meth)acryloyloxy groups, a urethane bond, and a linear polyoxyalkylene chain in one molecule. The total proportion of monomer a and monomer b to the total amount of monomer x is preferably 50 to 100% by mass, more preferably 70 to 100% by mass. Within the above range, a patch having superior moisture permeability and water resistance can be obtained. The proportion of monomer a relative to the total amount of monomer x is preferably 50 to 100 mass %, more preferably 70 to 100 mass %. Within the above range, a patch having superior moisture permeability and water resistance can be obtained. The mass ratio of monomer a to monomer b in monomer x, monomer a / monomer b, is preferably 50 / 50 to 100 / 0, more preferably 70 / 30 to 100 / 0, and even more preferably 80 / 20 to 99 / 1. Within the above ranges, a patch having superior moisture permeability and water resistance can be obtained.

[0022] <Monomer a> Monomer a has one (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain in one molecule. The monomer a constituting the polymer A may be two or more kinds.

[0023] Monomer a can be obtained, for example, by the following three production methods (1) to (3). (1) Monomer a is obtained by a urethane reaction between a compound having one hydroxyl group and a linear polyoxyalkylene chain, and a compound having a (meth)acryloyloxy group and an isocyanate group. (2) Monomer a is obtained by subjecting a compound having one hydroxyl group and a linear polyoxyalkylene chain to a urethane reaction with a compound having two isocyanate groups to obtain a prepolymer having an isocyanate group at its terminal, and then subjecting the isocyanate group of the prepolymer to a urethane reaction with a compound having one hydroxyl group and a (meth)acryloyloxy group. (3) Monomer a is obtained by a urethane reaction between one hydroxyl group of a compound having two hydroxyl groups and a linear polyoxyalkylene chain and a compound having a (meth)acryloyloxy group and an isocyanate group. The patch of the present invention has an adhesive layer containing a polymer having structural units based on monomer a, and thus has excellent moisture permeability even if the content of ethylene oxide units in the polymer is low.

[0024] The proportion of (meth)acryloyloxy groups to the total amount of monomer a is preferably 0.15 to 7.0 mass%, more preferably 0.2 to 2.3 mass%, and even more preferably 0.22 to 1.7 mass%, from the viewpoints of the curability of the curable composition containing monomer a and the flexibility of the resulting polymer. The ratio of the urethane bond to the total amount of the monomer a is preferably 0.15 to 1.6 mass%, more preferably 0.18 to 2.2 mass%, and even more preferably 0.20 to 1.4 mass%, from the viewpoints of the curability of the curable composition containing the monomer a and the flexibility of the obtained polymer.

[0025] The Mn of the polyoxyalkylene chain in the monomer a is 1,000 or more, and from the viewpoint of the flexibility and adhesiveness of the resulting polymer, it is preferably from 1,000 to 25,000, more preferably from 3,000 to 24,500, and even more preferably from 4,000 to 24,000. The Mw / Mn of the polyoxyalkylene chain in the monomer a is preferably from 1.03 to 1.2, more preferably from 1.04 to 1.15, and even more preferably from 1.05 to 1.14, since the viscosity of the curable composition containing the monomer a becomes low.

[0026] The Mn and Mw / Mn of the polyoxyalkylene chain in monomer a are obtained by measuring the Mn and Mw of a compound having one hydroxyl group and a linear polyoxyalkylene chain, or a compound having two hydroxyl groups and a linear polyoxyalkylene chain, which is used in the three production methods.

[0027] Specifically, the urethane bond of monomer a is hydrolyzed under alkaline conditions, and the Mn and Mw of the resulting compound having one hydroxyl group and a linear polyoxyalkylene chain, or the compound having two hydroxyl groups and a linear polyoxyalkylene chain, are measured.

[0028] The content of ethylene oxide units in the polyoxyalkylene chain in the monomer a is 0 to 50% by mass, preferably 0 to 40% by mass, and more preferably 0 to 25% by mass. When the content of ethylene oxide units is equal to or less than the upper limit, the water resistance of the patch having an adhesive layer containing a polymer having a structural unit based on the monomer a is improved. The ethylene oxide content of the monomer a is 1 It can be calculated by H-NMR.

[0029] The content of the propylene oxide unit in the polyoxyalkylene chain in the monomer a is preferably from 50 to 100 mass %, more preferably from 60 to 100 mass %, and further preferably from 75 to 100 mass %.

[0030] The Mn of the monomer a is preferably 5,000 to 25,000, more preferably 6,000 to 24,500, and even more preferably 7,000 to 24,000. When the Mn of the monomer a is within the above range, the viscosity of the curable composition containing the monomer a is easily adjusted. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the obtained polymer is likely to be low, and the adhesiveness to the skin is likely to be good. When two or more types of monomer a are used, it is preferable that the Mn of each of them is within the above range. The Mw / Mn of the monomer a is preferably from 1.03 to 1.20, more preferably from 1.04 to 1.15, and further preferably from 1.05 to 1.14. When two or more kinds of monomer a are used, it is preferable that the Mw / Mn of each of them is within the above range.

[0031] When producing the monomer a, the water content in the raw material composition containing the compound having a linear polyoxyalkylene chain is preferably as low as possible, and is preferably 300 mass ppm or less, more preferably 250 mass ppm or less, and even more preferably 50 to 200 mass ppm, relative to the compound having a linear polyoxyalkylene chain. When the water content is within the above range, the generation of reaction products between water and the compound having an isocyanate group is small, and the stability of the obtained monomer a is improved. Furthermore, it is easy to suppress the change in appearance over time of the curable composition containing the monomer a, and the elastic modulus and adhesiveness to skin of the polymer obtained from the curable composition are likely to be good. The content of the reaction product between water and a compound having an isocyanate group is preferably 0.5 mass% or less, and more preferably 0.3 mass% or less, based on the total amount of the monomer a. % The following is more preferred:

[0032] In the production process of the monomer a, by-products other than the monomer a, such as the reaction product of the moisture and the isocyanate group-containing compound, may be generated in the product (hereinafter referred to as "product a"). The total proportion of by-products in product a is preferably 20% by mass or less, more preferably 15% by mass or less, and most preferably 0% by mass. When it is 20% by mass or less, the function of monomer a is sufficiently exhibited, so that product a can be regarded as monomer a.

[0033] Examples of the monomer a include a monomer a-1 represented by the following formula 3, a monomer a-2 represented by the following formula 4, and a monomer a-3 described below.

[0034] Monomer a-1 is obtained by a urethane reaction between a compound having one hydroxyl group and a linear polyoxyalkylene chain, represented by the following formula 3a (hereinafter referred to as "compound 3a"), and a compound having a (meth)acryloyloxy group and an isocyanate group, represented by the following formula 3b (hereinafter referred to as "compound 3b").

[0035] Since each of compound 3a and compound 3b has one group capable of undergoing a urethanization reaction in one molecule, it is easy to control the number of urethane bonds in one molecule of monomer a-1 to one. If the number of urethane bonds in one molecule of monomer a-1 is small, the viscosity of the curable composition containing monomer a is likely to be low. Therefore, it is more preferable that monomer a contains monomer a-1, in that the curable composition has a low viscosity and a polymer having excellent flexibility and adhesion to skin is easily obtained.

[0036] [ka]

[0037] [ka]

[0038] Compound 3a can be obtained by a known method of ring-opening addition polymerization of an alkylene oxide using a monohydric alcohol or a compound obtained by adding an alkylene oxide to a monohydric alcohol as an initiator, or by a known method of ring-opening addition polymerization of an alkylene oxide to an -OH group of a monocarboxylic acid. Specific examples of the alkylene oxide include propylene oxide, ethylene oxide, 1,2-butylene oxide, and 2,3-butylene oxide.

[0039] In the above formulas 3, 3a and 3b, R 11 is a hydrogen atom or a methyl group, and is preferably a hydrogen atom. -(OR 12 ) c - represents a linear polyoxyalkylene chain formed from alkylene oxide based units. R 12 is a linear or branched alkylene group having 2 to 4 carbon atoms, and multiple R 12 may be the same or different. Two or more types of R 12 If present, -OR 12 -The chain of R can be block or random. 12is preferably either one or both of an ethylene group and a propylene group. As the ethylene group and the propylene group, a 1,2-ethylene group and a 1,2-propylene group are preferable. R 13 is an alkyl group having 1 to 20 carbon atoms, or R 13 R represents a carboxylic acid residue having 1 to 20 carbon atoms together with an oxygen atom bonded to it. The carboxylic acid residue is a monovalent group obtained by removing one hydrogen atom from a monocarboxylic acid having 1 to 20 carbon atoms and including a carbon atom in the carboxy group. 13 In terms of ease of reaction, an alkyl group having 1 to 20 carbon atoms is preferred, and an alkyl group having 2 to 8 carbon atoms is more preferred. b is an integer of 1 to 8, and an integer of 1 to 4 is preferable. c is an integer of 20 to 600, preferably an integer of 35 to 500, and more preferably an integer of 65 to 250.

[0040] The hydroxyl value of the compound 3a is preferably 2.3 mgKOH / g or more and less than 56.1 mgKOH / g, more preferably 3 to 14 mgKOH / g.The hydroxyl-equivalent molecular weight is preferably more than 1,000 and 25,000 or less, more preferably 4,000 to 15,000. When the hydroxyl-equivalent molecular weight of compound 3a is within the above range, Mn of monomer a-1 can be adjusted to the range of 5,000 to 25,000. When the hydroxyl-equivalent molecular weight of compound 3a is within the above range, the average number of functional groups of the resulting monomer a-1 can be easily adjusted to 0.8 to 1.3. The smaller the hydroxyl-equivalent molecular weight is, the easier it is to adjust the upper limit of the average number of functional groups to 1.3 or less.

[0041] In the production of compound 3a, it is not particularly necessary to remove moisture by degassing under reduced pressure, and the amount of moisture usually contained in the raw materials etc. put into the reaction system is acceptable. For example, usually, the lower the moisture content of the initiator, the more preferable, more preferably 500 mass ppm or less, and even more preferably 300 mass ppm or less. When the moisture content is within this range, the amount of diol produced from water is suppressed, and the amount of by-products in which (meth)acryloyloxy groups are added to the diol is finally suppressed, and the upper limit of the average functionality of product a-1 including the by-products and monomer a-1 is easily adjusted to 1.3 or less.

[0042] Compound 3b may be a commercially available product. For example, Karenz-AOI (R 11 = H, b = 2), Karens-MOI (R in Eq. 3b) 11 =CH3, b=2) (both are product names of Showa Denko K.K.). The reaction between compound 3a and compound 3b is a urethane reaction, which can be carried out by a known method. When reacting these, the compounding ratio of compound 3b to compound 3a is preferably 80 to 100, more preferably 90 to 100, and most preferably 100, in terms of index (NCO / OH ratio). By setting the index within the above range, the average number of functional groups of product a-1 can be easily adjusted to the range of 0.8 to 1.3. Compound 3a may be a mixture of two or more kinds, in which case each compound 3a is preferably a compound within the above-mentioned category.

[0043] The ratio of the monomer a-1 to the total amount of the product a-1 is preferably 80% by mass or more, more preferably 85 to 100% by mass, so that the function of the monomer a is sufficiently exhibited. When the product a-1 contains the monomer a-1 in the above ratio, the function of the monomer a is sufficiently exhibited, so that the product a-1 can be regarded as the monomer a-1.

[0044] The Mn of the monomer a-1 is preferably 5,000 to 25,000, more preferably 6,000 to 24,500, and even more preferably 7,000 to 24,000. When the Mn of the monomer a-1 is within the above range, the viscosity of the curable composition containing the monomer a-1 is easily adjusted. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the resulting polymer is likely to be low, and the adhesiveness to the skin is likely to be good. When two or more kinds of monomers a-1 are used, it is preferable that the Mn of each of them is within the above range. The Mw / Mn of the monomer a-1 is preferably from 1.03 to 1.20, more preferably from 1.04 to 1.15, and further preferably from 1.05 to 1.14. When two or more kinds of monomer a-1 are used, it is preferable that the Mw / Mn of each of them is within the above range.

[0045] The Mn of the product a-1 is preferably 5,000 to 25,000, more preferably 6,000 to 24,500, and even more preferably 7,000 to 24,000. When the Mn of the product a-1 is within the above range, it is easy to adjust the viscosity of the curable composition containing the product a-1. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the obtained polymer is likely to be low, and the adhesion to the skin is likely to be good. When two or more types of product a-1 are used, it is preferable that the Mn of each is within the above range. The Mw / Mn of the product a-1 is preferably from 1.03 to 1.20, more preferably from 1.04 to 1.15, and even more preferably from 1.05 to 1.14. When two or more types of product a-1 are used, it is preferable that the Mw / Mn of each is within the above range.

[0046] When the product a-1 can be regarded as the monomer a-1, the average number of functional groups calculated from the Mn and the number of functional groups of the product a-1 can be regarded as the average number of functional groups of the monomer a-1. In this case, the average number of functional groups in the product a-1 is preferably 0.8 to 1.3, more preferably 0.9 to 1.2. The product a-1 within the above range is likely to reduce shrinkage during curing, is likely to reduce the elastic modulus of the resulting polymer, and is likely to have good adhesion to the skin.

[0047] The monomer a-1 is a compound represented by the formula 3, and R 12 It is preferable that the monomer a-1-PO contains a monomer a-1-PO having a propylene group ratio of 50 to 100 mass % based on the total amount of the monomer a-1-PO.

[0048] In the monomer a-1-PO, R 12 The proportion of propylene groups in the total amount of R is more preferably 57 to 100 mass%, particularly preferably 100 mass%. 12 Among these, the alkylene group other than the propylene group is preferably an ethylene group. 12 When R contains an ethylene group, 12 The proportion of propylene groups to the total amount is preferably from 66 to 99 mass %, more preferably from 74 to 95 mass %. R of monomer a-1-PO 12 The proportion of ethylene groups relative to the total amount is preferably from 0 to 43 mass %, more preferably from 1 to 34 mass %, and even more preferably from 5 to 26 mass %.

[0049] When the monomer a-1-PO is used, the proportion of the monomer a-1-PO relative to the total amount of the monomer a is preferably 50 to 100 mass%, more preferably 80 to 100 mass%. When the proportion of the monomer a-1-PO is equal to or more than the lower limit of the above range, the curable composition containing the monomer a-1-PO has a lower viscosity, and the obtained polymer has better flexibility.

[0050] Monomer a-2 can be obtained by subjecting a compound having one hydroxyl group represented by the following formula 4a and a linear polyoxyalkylene chain (hereinafter referred to as "compound 4a") to a urethane reaction with a compound having two isocyanate groups represented by the following formula 4b (hereinafter referred to as "compound 4b") to obtain a prepolymer having an isocyanate group at its end (isocyanate group-terminated urethane prepolymer), and then reacting the isocyanate group of the prepolymer with a compound having one hydroxyl group represented by the following formula 4c and a (meth)acryloyloxy group (hereinafter referred to as "compound 4c"):

[0051] [ka]

[0052] [ka]

[0053] Compound 4a can be obtained by a known method of ring-opening addition polymerization of an alkylene oxide using a monohydric alcohol or a compound obtained by adding an alkylene oxide to a monohydric alcohol as an initiator, or by a known method of ring-opening addition polymerization of an alkylene oxide to a hydroxyl group of a monocarboxylic acid. Specific examples of the alkylene oxide include propylene oxide, ethylene oxide, 1,2-butylene oxide, and 2,3-butylene oxide.

[0054] In the above formulas 4 and 4c, R 21 is a hydrogen atom or a methyl group, and is preferably a hydrogen atom. -(OR 22 ) e - represents a linear polyoxyalkylene chain formed from alkylene oxide based units. R 22 is a linear or branched alkylene group having 2 to 4 carbon atoms, and multiple R 22 may be the same or different. Two or more types of R 22 If present, -OR 22-The chain of R can be block or random. 22 is preferably either one or both of an ethylene group and a propylene group. As the ethylene group and the propylene group, a 1,2-ethylene group and a 1,2-propylene group are preferable. R 23 is an alkyl group having 1 to 20 carbon atoms, or R 23 R represents a carboxylic acid residue having 1 to 20 carbon atoms together with an oxygen atom bonded to it. The carboxylic acid residue is a monovalent group formed by removing one hydrogen atom from a monocarboxylic acid having 1 to 20 carbon atoms including a carbon atom in the carboxy group. 23 In terms of ease of reaction, an alkyl group having 1 to 20 carbon atoms is preferred, and an alkyl group having 2 to 8 carbon atoms is more preferred.

[0055] R 24 is a divalent group obtained by removing an isocyanate group from compound 4b. Examples of compound 4b include compounds having two isocyanate groups, such as non-yellowing aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and various modified products of these dipolyisocyanates (modified products having two isocyanate groups). Two or more types of diisocyanates can also be used in combination. As the diisocyanate, an aliphatic diisocyanate or an alicyclic diisocyanate is preferable since it has excellent light resistance, weather resistance, and heat resistance and can maintain transparency. Examples of non-yellowing aromatic diisocyanates include xylylene diisocyanate and tetramethyl xylylene diisocyanate. Examples of aliphatic diisocyanates include 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate and lysine diisocyanate. Examples of alicyclic diisocyanates include isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,5-norbornane diisocyanate and 2,6-norbornane diisocyanate. As the compound 4b, isophorone diisocyanate and 1,6-hexamethylene diisocyanate are preferable. d is an integer of 1 to 8, and preferably an integer of 1 to 4. e is an integer of 20 to 600, and preferably an integer of 35 to 500, and more preferably an integer of 65 to 250.

[0056] The compound 4a has a hydroxyl value of preferably 2.3 mgKOH / g or more and less than 56.1 mgKOH / g, more preferably 3 to 14 mgKOH / g, and a hydroxyl-equivalent molecular weight of preferably more than 1,000 and not more than 25,000, more preferably 4,000 to 15,000. By setting the hydroxyl-calculated molecular weight of the compound 4a within the above range, the Mn of the monomer a-2 can be adjusted to the range of 5,000 to 25,000. Compound 4a may be a mixture of two or more kinds, in which case each compound 4a is preferably a compound within the above-mentioned category.

[0057] The amount of water and the molecular weight when compound 4a is produced are the same as those of compound 3a. In the production of compound 4a, as in the case of compound 3a, a by-product in which a (meth)acryloyloxy group is added to a diol generated from water contained in the raw material and a product containing monomer a-2 (hereinafter referred to as "product a-2") may be obtained.

[0058] The reaction of compound 4a and compound 4b to obtain a prepolymer having an isocyanate group at the end (isocyanate group-terminated urethane prepolymer) is a urethane reaction, which can be carried out by a known method. The compounding ratio of compound 4b to compound 4a when reacting them is preferably 100 to 200, more preferably 180 to 200, and most preferably 200, in terms of index (NCO / OH ratio).

[0059] The reaction between the obtained isocyanate-terminated urethane prepolymer and compound 4c is a urethane reaction, which can be carried out by a known method.

[0060] When reacting these, the compounding ratio of the prepolymer and the compound 4c is preferably 1:1.0 to 1:1.1, more preferably 1:1.0 to 1:1.05, in terms of the molar ratio of the isocyanate group in the prepolymer to the hydroxyl group in the compound 4c. Within the above range, the average number of functional groups of the product a-2 can be easily adjusted to the range of 0.8 to 1.2. The ratio of the monomer a-2 to the total mass of the product a-2 is preferably 80% by mass or more, more preferably 85 to 100% by mass, in order to fully exert the function of the monomer a. When the product a-2 contains the monomer a-2 in the above ratio, the function of the monomer a is fully exerted, and therefore the product a-2 can be regarded as the monomer a-2.

[0061] The Mn of the monomer a-2 is preferably 5,000 to 25,000, more preferably 6,000 to 24,500, and even more preferably 7,000 to 24,000. When the Mn of the monomer a-2 is within the above range, it is easy to adjust the viscosity of the curable composition containing the monomer a-2. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the obtained polymer is likely to be low, and the adhesiveness to the skin is likely to be good. When two or more kinds of monomers a-2 are used, it is preferable that the Mn of each of them is within the above range. The Mw / Mn of the monomer a-2 is preferably from 1.03 to 1.20, more preferably from 1.04 to 1.15, and further preferably from 1.05 to 1.14. When two or more kinds of monomers a-2 are used, it is preferable that the Mw / Mn of each of them is within the above range.

[0062] The Mn of the product a-2 is preferably 5,000 to 25,000, more preferably 6,000 to 24,500, and even more preferably 7,000 to 24,000. When the Mn of the product a-2 is within the above range, it is easy to adjust the viscosity of the curable composition containing the product a-2. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the obtained polymer is likely to be low, and the adhesion to the skin is likely to be good. When two or more types of product a-2 are used, it is preferable that the Mn of each is within the above range. The Mw / Mn of the product a-2 is preferably from 1.03 to 1.20, more preferably from 1.04 to 1.15, and even more preferably from 1.05 to 1.14. When two or more types of product a-2 are used, it is preferable that the Mw / Mn of each is within the above range.

[0063] When the product a-2 can be regarded as the monomer a-2, the average number of functional groups calculated from the Mn and the number of functional groups of the product a-2 can be regarded as the average number of functional groups of the monomer a-2. In this case, the average number of functional groups in the product a-2 is preferably 0.8 to 1.3, more preferably 0.9 to 1.2. The product a-2 within the above range is likely to reduce shrinkage during curing, is likely to reduce the elastic modulus of the resulting polymer, and is likely to have good adhesion to the skin.

[0064] The monomer a-2 is a compound represented by the formula 4, and R 22 It is preferable that the monomer a-2-PO contains a monomer a-2-PO having a propylene group ratio of 50 to 100 mass % based on the total amount of the monomer a-2-PO.

[0065] In the monomer a-2-PO, R 22 The proportion of propylene groups in the total amount of R is more preferably 57 to 100 mass%, particularly preferably 100 mass%. 22 Among these, it is preferable that the alkylene group other than the propylene group is an ethylene group. 22 When R contains an ethylene group, 22 The proportion of propylene groups to the total amount is preferably from 66 to 99 mass %, more preferably from 74 to 95 mass %. R of monomer a-2-PO 22 The proportion of ethylene groups relative to the total amount is preferably from 0 to 43 mass %, more preferably from 1 to 34 mass %, and even more preferably from 5 to 26 mass %.

[0066] When the monomer a-2-PO is used, the proportion of the monomer a-2-PO relative to the total amount of the monomer a is preferably 50 to 100 mass%, more preferably 80 to 100 mass%. When the proportion of the monomer a-2-PO is equal to or more than the lower limit of the above range, the curable composition containing the monomer a-2-PO has a lower viscosity, and the obtained polymer has better flexibility.

[0067] Monomer a-3 is a monomer having one functional group, obtained by a urethane reaction between a compound having two hydroxyl groups and a linear polyoxyalkylene chain (hereinafter referred to as "compound 5a") and the compound 3b.

[0068] Compound 5a is a polyoxyalkylene diol obtained by ring-opening addition polymerization of alkylene oxide using a dihydric alcohol or a compound obtained by adding alkylene oxide to a dihydric alcohol as an initiator. Compound 5a has an initiator residue, a polyoxyalkylene chain, and hydroxyl groups corresponding to the number of alcoholic hydroxyl groups of the initiator. The ring-opening addition polymerization of dihydric alcohol and alkylene oxide, and the ring-opening addition polymerization of initiator and alkylene oxide can be carried out by a conventional method in the presence of a catalyst such as an alkaline catalyst such as KOH or a composite metal cyanide complex catalyst. The number of carbon atoms in the dihydric alcohol is preferably 1 to 12, and more preferably 2 to 8. Specific examples of the dihydric alcohol include ethylene glycol, propylene glycol, polypropylene glycol such as dipropylene glycol, and 1,4-butanediol.

[0069] The number of carbon atoms in the alkylene oxide unit present in the compound 5a is preferably 2 to 4. Specific examples include propylene oxide, ethylene oxide, 1,2-butylene oxide, and 2,3-butylene oxide. The alkylene oxide units present in one molecule may be the same or different. When two or more types of alkylene oxide unit chains are present in one molecule, they may be block chains or random chains. The alkylene oxide units are preferably either one or both of ethylene oxide units and propylene oxide units. The ratio of propylene oxide units to the total amount of alkylene oxide units is preferably 57 to 100 mass%, more preferably 100 mass%. Of the alkylene oxide units present in one molecule, alkylene oxide units other than propylene oxide units are preferably ethylene oxide units. When the alkylene oxide units contain an ethylene group, the ratio of propylene groups to the total amount of alkylene oxide units is preferably 66 to 99 mass%, more preferably 74 to 95 mass%. The proportion of ethylene groups relative to the total amount of alkylene oxide units is preferably from 0 to 43 mass%, more preferably from 1 to 34 mass%, and even more preferably from 5 to 26 mass%.

[0070] The compound 5a has a hydroxyl value of preferably 1.6 to 56.1 mgKOH / g, more preferably 3.7 to 14 mgKOH / g, and a hydroxyl-equivalent molecular weight of preferably more than 1,000 and not more than 25,000, more preferably 4,000 to 15,000. When the hydroxyl-equivalent molecular weight of compound 5a is within the above range, Mn of monomer a-3 can be adjusted to the range of 5,000 to 25,000. When the hydroxyl-equivalent molecular weight of compound 5a is within the above range, the average functionality of monomer a-3 to be produced can be easily adjusted to 0.8 to 1.3. The smaller the hydroxyl-equivalent molecular weight, the easier it is to adjust the upper limit of the average functionality to 1.3 or less. Compound 5a may be a mixture of two or more polyoxyalkylene diols, in which case each of the polyoxyalkylene diols is preferably a compound within the above category.

[0071] The reaction between compound 5a and compound 3b is a urethane reaction, and can be carried out by a known method. In such a reaction, the hydroxyl groups at both ends of compound 5a can react with compound 3b, and thus a product containing a monomer with two functional groups (hereinafter referred to as "product a-3") can be produced as a by-product in addition to a monomer with one functional group. The average number of functional groups in the product a-3 is preferably from 0.8 to 1.3, and more preferably from 0.9 to 1.2.

[0072] In this reaction, the compounding ratio of compound 3b to compound 5a is preferably 30 to 50 in terms of index (NCO / OH ratio), more preferably 40 to 50, and most preferably 50. When the index is within the above range, a compound in which one molecule of compound 5a reacts with one molecule of compound 3b is easily obtained, and the average number of functional groups of the product a-3 is easily adjusted to the range of 0.8 to 1.3.

[0073] The ratio of monomer a-3 to the total amount of product a-3 is preferably 80% by mass or more, more preferably 85 to 100% by mass, in order to fully exert the function of monomer a. When product a-3 contains monomer a-3 in a ratio within the above range, the function of monomer a is fully exerted, and product a-3 can be regarded as monomer a-3.

[0074] When the product a-3 can be regarded as the monomer a-3, the average number of functional groups calculated from the Mn and the number of functional groups of the product a-3 can be regarded as the average number of functional groups of the monomer a-3. In this case, the average number of functional groups in the product a-3 is preferably 0.8 to 1.3, more preferably 0.9 to 1.2. The product a-3 within the above range is likely to reduce shrinkage during curing, is likely to reduce the elastic modulus of the resulting polymer, and is likely to have good adhesion to the skin.

[0075] The Mn of the monomer a-3 is preferably 5,000 to 25,000, more preferably 6,000 to 24,500, and even more preferably 7,000 to 24,000. When the Mn of the monomer a-3 is within the above range, it is easy to adjust the viscosity of the curable composition containing the monomer a-3. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the obtained polymer is likely to be low, and the adhesion to the skin is likely to be good. When two or more kinds of monomer a-3 are used, it is preferable that Mn of each of them is within the above range. The Mw / Mn of the monomer a-3 is preferably from 1.03 to 1.20, more preferably from 1.04 to 1.15, and further preferably from 1.05 to 1.14. When two or more kinds of monomer a-3 are used, it is preferable that the Mw / Mn of each of them is within the above range.

[0076] The Mn of the product a-3 is preferably 5,000 to 25,000, more preferably 6,000 to 24,500, and even more preferably 7,000 to 24,000. When the Mn of the product a-3 is within the above range, it is easy to adjust the viscosity of the curable composition containing the product a-3. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the obtained polymer is likely to be low, and the adhesiveness to the skin is likely to be good. When two or more types of product a-3 are used, it is preferable that the Mn of each is within the above range. The Mw / Mn of the product a-3 is preferably from 1.03 to 1.20, more preferably from 1.04 to 1.15, and even more preferably from 1.05 to 1.14. When two or more types of product a-3 are used, it is preferable that the Mw / Mn of each is within the above range.

[0077] The proportion of the monomer a-1 relative to the total amount of the monomer a is preferably from 50 to 100 mass %, more preferably from 75 to 100 mass %, and further preferably from 80 to 100 mass %. The proportion of the monomer a-2 relative to the total amount of the monomer a is preferably from 0 to 50 mass %, more preferably from 0 to 25 mass %, and further preferably from 0 to 20 mass %. The proportion of the monomer a-3 relative to the total amount of the monomer a is preferably from 0 to 50 mass %, more preferably from 0 to 25 mass %, and further preferably from 0 to 20 mass %.

[0078] The monomer a particularly preferably includes at least one selected from the group consisting of monomer a-1 and monomer a-2. The total proportion of the monomer a-1 and the monomer a-2 relative to the total amount of the monomer a is preferably 50% by mass or more, more preferably 80% by mass or more, and particularly preferably 100% by mass. When the total ratio of the monomer a-1 and the monomer a-2 is equal to or greater than the lower limit of the range, the curing shrinkage is reduced effectively, the flexibility of the resulting polymer is increased, and the adhesiveness to the skin is improved. The mass ratio of the monomer a-1 and the monomer a-2, (a-1):(a-2), is preferably 1:0 to 1:1.

[0079] <Monomer b> Monomer b has two (meth)acryloyloxy groups, a urethane bond, and a linear polyoxyalkylene chain in one molecule. From the viewpoint of the curing rate, it is preferable that the monomer b has an acryloyloxy group. The monomer b constituting the polymer A may be two or more kinds.

[0080] Monomer b can be obtained, for example, by the following two production methods (i) and (ii). (i) Monomer b is obtained by a urethane reaction between a compound having two hydroxyl groups and a linear polyoxyalkylene chain and a compound having a (meth)acryloyloxy group and an isocyanate group. (ii) Monomer b is obtained by subjecting a compound having two hydroxyl groups and a linear polyoxyalkylene chain to a urethane reaction with a compound having two isocyanate groups to obtain a prepolymer having isocyanate groups at both ends, and then subjecting the isocyanate groups of the prepolymer to a urethane reaction with a compound having one hydroxyl group and a (meth)acryloyloxy group.

[0081] In the production methods (i) and (ii), the compound having two hydroxyl groups and a linear polyoxyalkylene chain can be the compound 5a. In the production method (i), the compound having a (meth)acryloyloxy group and an isocyanate group can be the compound 3b. In the production method (ii), the compound having two isocyanate groups can be the above-mentioned compound 4b. In the production method (ii), the compound having one hydroxyl group and a (meth)acryloyloxy group can be the compound 4c. The patch of the present invention has an adhesive layer containing a polymer having structural units based on monomer b, and thus has excellent moisture permeability even if the content of ethylene oxide units in the polymer is low.

[0082] The number of urethane bonds in one molecule of monomer b is one or more. The content of the urethane bond relative to the total amount of the monomer b is preferably 3.90 to 6.00 mass%, more preferably 3.92 to 5.70 mass%, and further preferably 3.95 to 5.50 mass%. By having such a high concentration (abundance ratio) of the urethane bond, the adhesiveness of the obtained polymer can be improved. The content of urethane bonds relative to the total amount of monomer b is calculated in the same manner as the content of urethane bonds relative to the total amount of monomer a.

[0083] The Mn of the polyoxyalkylene chain in the monomer b is 1,000 or more, and from the viewpoint of flexibility and low viscosity of the resulting polymer, it is preferably 1,000 to 35,000, more preferably 5,000 to 30,000, and even more preferably 8,000 to 25,000. The Mw / Mn of the polyoxyalkylene chain in the monomer b is preferably from 1.01 to 1.30, more preferably from 1.03 to 1.20, and even more preferably from 1.02 to 1.10, since the curable composition containing the monomer b is likely to have a lower viscosity.

[0084] The Mn and Mw / Mn of the polyoxyalkylene chain in the monomer b are obtained by measuring the Mn and Mw of the compound having two hydroxyl groups and a linear polyoxyalkylene chain used in the two production methods. Specifically, it can be measured in the same manner as in the measurement of Mn and Mw / Mn of the polyoxyalkylene chain in the monomer a.

[0085] The Mn of the monomer b is preferably 1,000 to 35,000, more preferably 6,000 to 30,000, and further preferably 9,000 to 25,000. When the Mn of the monomer b is within the above range, the viscosity of the curable composition is easily adjusted, and the adhesiveness of the obtained polymer is likely to be good. When the curable composition contains two or more types of monomer b, it is preferable that Mn of each of the monomers b is within the above range. The Mw / Mn of the monomer b is preferably from 1.01 to 1.30, more preferably from 1.03 to 1.20. When the curable composition contains two or more types of monomer b, it is preferable that the Mw / Mn of each is within the above range.

[0086] In the production process of monomer b, by-products other than monomer b may be generated in the product (hereinafter referred to as "product b"). The content of the by-product in the product b is preferably 20% by mass or less, more preferably 15% by mass or less, preferably 10% by mass or less, and most preferably 0. When the content is 20% by mass or less, the function of the monomer b is sufficiently exhibited, and the product b can be regarded as the monomer b.

[0087] The Mn of the product b is preferably 1,000 to 35,000, more preferably 6,000 to 30,000, and even more preferably 9,000 to 25,000. When the Mn of the product b is within the above range, it is easy to adjust the viscosity of the curable composition containing the product b. When the Mn is equal to or greater than the lower limit of the above range, the cure shrinkage rate of the obtained polymer is likely to be low, and the adhesiveness to the skin is likely to be good. When two or more types of product b are used, it is preferable that the Mn of each of them is within the above range. The Mw / Mn of the product b is preferably from 1.01 to 1.30, and more preferably from 1.03 to 1.20. When two or more types of product b are used, it is preferable that the Mw / Mn of each of them is within the above range.

[0088] When the product b can be regarded as the monomer b, the average functionality calculated from the Mn and the number of functional groups of the product b can be regarded as the average functionality of the monomer b. In this case, the average functionality of the product b is preferably 1.6 to 2.0, more preferably 1.7 to 2.0, and even more preferably 1.8 to 1.96. When the product b is within the above range, the adhesiveness of the resulting polymer tends to be good.

[0089] The monomer b preferably contains a monomer b-PO having an oxypropylene group content of 57 to 100 mass % and an oxyethylene group content of 0 to 43 mass % based on the total oxyalkylene groups. When the monomer b-PO is used, the content of the monomer b-PO relative to the monomer b is preferably 50 to 100 mass%, more preferably 80 to 100 mass%. When the content of the monomer b-PO is within the above range, flexibility is easily obtained in the obtained polymer.

[0090] In particular, the monomer b-PO is preferably a reaction product of a polyoxyalkylene diol having an oxypropylene group content of 80 to 100 mass% and an oxyethylene group content of 0 to 20 mass% relative to all oxyalkylene groups, an average number of hydroxyl groups of 2 to 3, and a number average molecular weight of 1,000 to 35,000, a non-yellowing diisocyanate, and a hydroxyalkyl acrylate. The non-yellowing diisocyanate is preferably a diisocyanate selected from the group consisting of aliphatic diisocyanates, alicyclic diisocyanates, and non-yellowing aromatic diisocyanates, specifically, for example, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and xylylene diisocyanate. As the hydroxyalkyl acrylate, the following compound 2 is preferred. CH2=CH-C(=O)O-R' …(2) R' represents a group in which one hydrogen atom of an alkyl group having 1 to 6 carbon atoms has been substituted with a hydroxyl group. Specific examples of compound 2 include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0091] <Adhesive layer> The pressure-sensitive adhesive layer of this embodiment contains a polymer A. The polymer A has a constituent unit based on a monomer x. The polymer of this embodiment is obtained by a polymerization reaction of the monomer x. The polymerization can be carried out by a known method using a curable composition containing the monomer x, a thermal polymerization initiator, a photopolymerization initiator, and other components as necessary.

[0092] The polymer A may have units based on other monomers in addition to the units based on the monomer x. The other monomers may be any monomers as long as they are copolymerizable with the monomer x. Examples of the other monomers include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate, aliphatic (meth)acrylates such as butyl (meth)acrylate and lauryl (meth)acrylate, acrylamides such as dimethylacrylamide, isopropylacrylamide and acryloylmorpholine, and (meth)acrylates having a cyclic skeleton such as isoboron (meth)acrylate, tetrahydroxyfuran (meth)acrylate and cyclohexyl (meth)acrylate.

[0093] The ratio of units based on monomer x to all structural units of polymer A is preferably 50 to 100 mass%, more preferably 70 to 100 mass%, and even more preferably 80 to 100 mass%. When it is equal to or more than the lower limit of the above range, the moisture permeability and water resistance of a patch having a pressure-sensitive adhesive layer containing polymer A are improved.

[0094] The polymer A can be obtained by polymerizing a curable composition containing a monomer x. The curable composition of the present embodiment may be a photocurable resin composition or a thermosetting resin composition. When the curable composition is a thermosetting resin composition, it is preferable to contain a thermal polymerization initiator. When the curable composition is a photocurable resin composition, it is preferable to contain a photopolymerization initiator. Photocurable resin compositions are preferable because they can be polymerized at low temperatures and have a high polymerization rate. If the composition is a photocurable resin composition, a polymer can be obtained in a shorter time, and the productivity of the patch is superior.

[0095] (Photopolymerization initiator) As the photopolymerization initiator, a photopolymerization initiator that is sensitive to ultraviolet light having a wavelength of 380 nm or less is preferred from the viewpoint of ease of control of the polymerization reaction. Examples of the photopolymerization initiator include the photopolymerization initiators described in

[0147] to

[0151] of WO 2018 / 173896. As the photopolymerization initiator, a hydrogen abstraction type photopolymerization initiator is preferable, in which a photoexcited initiator and a hydrogen donor in the system form an exciplex and transfer the hydrogen of the hydrogen donor.Specific examples of the hydrogen abstraction type photopolymerization initiator include benzophenone, 4-methyl-benzophenone, 2,4,6-trimethylbenzophenone, 4-phenylbenzophenone, 3,3-dimethyl-4-methoxybenzophenone, 4-(meth)acryloyloxybenzophenone, 4-[2-((meth)acryloyloxy)ethoxy]benzophenone, 4-(meth)acryloyloxy-4'-methoxybenzophenone, methyl 2-benzoylbenzoate, and methyl benzoylformate. Two or more kinds of photopolymerization initiators may be used in combination.

[0096] The amount of the photopolymerization initiator used is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the monomer x. When the amount of the photopolymerization initiator used is within the above range, it is easy to obtain an appropriate reaction sensitivity to active energy rays.

[0097] (Thermal polymerization initiator) As the thermal polymerization initiator, an azo-based initiator or a peroxide-based initiator is preferred from the viewpoint of reactivity. Examples of the thermal polymerization initiator include the thermal polymerization initiators described in JP-A-2020-35451 and JP-A-2020-8877. Two or more types of thermal polymerization initiators may be used in combination.

[0098] The amount of the thermal polymerization initiator used is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the monomer x. When the amount of the thermal polymerization initiator used is within the above range, appropriate reaction sensitivity is easily obtained during heat curing.

[0099] (Other Ingredients) The curable composition of the present embodiment may contain conventionally known components as necessary as components other than the monomer x, the photopolymerization initiator, and the thermal polymerization initiator. Examples of other components include silane coupling agents, tackifier resins, antioxidants, light stabilizers, metal deactivators, rust inhibitors, antiaging agents, moisture absorbents, hydrolysis inhibitors, antistatic agents, antifoaming agents, and inorganic particles. If necessary, a reaction catalyst (such as a tertiary amine compound, a quaternary ammonium compound, or a tin laurate compound) may be contained. If necessary, a polyfunctional isocyanate (such as a modified product of isophorone diisocyanate, a modified product of hexamethylene diisocyanate, or a modified product of tolylene diisocyanate) may be contained. If necessary, a solvent may be contained.

[0100] The order of mixing the components is not particularly limited. The polymerization of the monomer x may be carried out by irradiating the components with ultraviolet light or by heat treatment after mixing the components. The components constituting the curable composition may be mixed in advance or may be mixed immediately before polymerization. For example, the photopolymerization initiator may be added to a premix in which components other than the photopolymerization initiator are mixed in advance, immediately before polymerization. The curable composition of the present embodiment can be used without containing a solvent. If necessary, the curable composition may contain a solvent. The solvent used is preferably removed during or after polymerization.

[0101] The polymer A can be obtained, for example, by forming the curable composition into a desired shape and irradiating it with ultraviolet light to polymerize the monomer x. Examples of methods for molding the curable composition include a method of coating on a support, a method of extrusion molding, and a method of pouring into a mold, which will be described later. The UV irradiation dose is 0.1 to 5 J / cm 2 is preferable, and 0.3 to 4 J / cm 2 More preferably, 0.5 to 3 J / cm 2 When the irradiation amount is equal to or more than the lower limit of the above range, the strength of the resulting pressure-sensitive adhesive layer is better, and when it is equal to or less than the upper limit, discoloration is unlikely to occur.

[0102] The proportion of the monomer x relative to the total amount of the curable composition is preferably from 50 to 100 mass %, more preferably from 70 to 100 mass %, and further preferably from 80 to 100 mass %.

[0103] The proportion of polymer A relative to the total amount of the pressure-sensitive adhesive layer is preferably 50 to 100 mass%, more preferably 70 to 100 mass%, and even more preferably 80 to 100 mass%. The pressure-sensitive adhesive layer of the present embodiment may contain, as components other than polymer A, (other components) described in the curable composition.

[0104] The moisture permeability of the adhesive layer is 2,500g / (m 2 ·day) or more, and 3,000g / (m 2 ·day) or more is preferable, and 3,500g / (m 2 ·days or more is preferable.

[0105] Moisture permeability is the rate at which water vapor passes through a test piece (1m 2 Calculate the amount per day. The moisture permeability was measured in an atmosphere of 40°C, with the relative humidity of one side of the space separated by the test piece at 90% and the other side of the space kept dry with a moisture absorbent. The mass (g) of water vapor passing through the test piece in 24 hours (1 day) was measured. 2The measurement is carried out according to JIS Z 0208:1976 Moisture permeability test method for moisture-proof packaging materials (cup method), and a circular test piece with a diameter about 10 mm larger than the inside diameter of the cup is placed over a cup containing about 50 g of calcium chloride moisture absorbent, and then a rubber packing and ring are placed over the test piece and screwed in place to prevent it from slipping. After measuring the total mass of this test piece, it is placed in a constant temperature and humidity chamber at 40°C and 90% RH, and the change in mass is measured at regular intervals, and the moisture permeability is calculated according to the following formula. Moisture permeability (g / (m 2 ·day))=W×240000 / S where S is the moisture permeability area (cm 2 ) and W represents the mass gain per hour (g / hr).

[0106] The moisture permeability of the adhesive layer can be calculated from the moisture permeability of the adhesive material formed by laminating the backing and the pressure-sensitive adhesive layer and the moisture permeability of the backing according to the following formula. (1 / Moisture permeability of adhesive layer)=(1 / Moisture permeability of patch)-(1 / Moisture permeability of support)

[0107] The thickness of the adhesive layer is preferably 10 to 40 μm, more preferably 12 to 35 μm, and even more preferably 15 to 30 μm. When the thickness of the adhesive layer is within the above range, the adhesive layer has better adhesion to the skin surface.

[0108] <Adhesive material> 1 is a cross-sectional view showing one embodiment of a patch according to the present invention. The patch 1 comprises a support 11 and a pressure-sensitive adhesive layer 12 provided on the surface of the support. Examples of the material of the support include urethane resins such as ether-based urethane resins and polyester-based urethane resins, polyamide resins such as polyether polyamide block polymers, acrylic resins such as polyacrylate, polyolefin resins such as polyethylene, polypropylene, and ethylene / vinyl acetate copolymers, and polyester resins such as polyether polyester. From the viewpoint of moisture permeability, the material of the support is preferably a urethane resin, a polyester resin, a polyamide resin, or a polyolefin resin, more preferably a urethane resin or an amide resin, and more preferably an ether-based urethane resin, a polyester-based urethane resin, or an amide resin. The material of the support can be used alone or in combination of two or more. The support is preferably in the form of a film, a porous film, a woven fabric or a nonwoven fabric. The support may be in the form of a laminated film in which substrate films made of different materials are laminated. The substrate film may be laminated with a fabric such as a woven fabric, a nonwoven fabric, a knitted fabric or a net. The thickness of the support is not particularly limited, but when a film is used as the support, the thickness is preferably 1 to 9 μm, more preferably 3 to 9 μm. When the thickness of the support is within this range, the moisture permeability of the support is excellent, the moisture permeability of the part where the support and the adhesive layer overlap is excellent, the patch is less likely to break, and the conformability of the patch to the skin surface is easily ensured. When a breathable cloth or film such as a nonwoven fabric, woven fabric, or porous film is used as the support, the thickness is preferably 10 to 250 μm, more preferably 20 to 150 μm. When the thickness of the support is within this range, the moisture permeability of the support is excellent, the moisture permeability of the part where the support and the adhesive layer overlap is excellent, the patch is less likely to break, and the conformability of the patch to the skin surface is easily ensured.

[0109] The moisture permeability of the support is 2,000g / (m 2 ·day) or more, and 3,500g / (m 2 ·day) or more is preferable, and 4,500g / (m 2 ·days or more is preferable.

[0110] The moisture permeability of the patch at the overlapping portion of the support and the adhesive layer is 2,000 g / (m 2 ·day) or more is preferable, and 2,800g / (m 2 ·day) or more is preferable, and 3,000g / (m 2 ·days or more is even more preferable.

[0111] In the patch 1 of the present embodiment, as shown in Fig. 1, a carrier 13 can be releasably laminated on the surface of the pressure-sensitive adhesive layer 12 opposite to the surface on which the support 11 is formed. The material of the carrier is not particularly limited, but preferred are plastic films such as polypropylene film, polyethylene film, and polyester film that has been subjected to a silicone release treatment or a fluorine release treatment, and paper base materials such as high-quality paper and glassine paper that have been subjected to a silicone release treatment or a fluorine release treatment.

[0112] The adhesive strength of the patch to human skin is preferably 0.1 to 1.2 N / 15 mm, and more preferably 0.2 to 0.8 N / 15 mm. The adhesive strength of a patch to human skin is measured according to the test method described in "10 Adhesive strength" of JIS Z 0237:2009, Test methods for adhesive tapes and adhesive sheets, by attaching a 15mm wide test piece to human skin in an atmosphere of 25°C, pressing it back and forth once at a speed of 300mm / min with a 2kg rubber roll, leaving it for 20 minutes, and then measuring the peel force at a peel angle of 90 degrees and a peel speed of 300mm / min.

[0113] Applications of the patch include wound covering materials, and suitable applications include medical dressing materials that are applied directly to the skin, film materials for fixing medical materials such as gauze, and patches for bandages. EXAMPLES

[0114] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following description.

[0115] <Measurement and evaluation methods> [Molecular weight measurement] The number average molecular weight (Mn) was measured by gel permeation chromatography (GPC) under the following conditions. Analytical equipment: HLC-8120GPC Tosoh Corporation product name Column: G7000HXL+GMHXL+GMHXL Tosoh product name Column size: 7.8mmφ×30cm each, total 90cm Column temperature: 40℃ ·Flow rate: 0.8mL / min ·Injection volume: 100μL Eluent: Tetrahydrofuran Detector: Differential refractometer (RI) Standard sample: polystyrene

[0116] [Evaluation of patch properties] The patches were evaluated for moisture permeability, adhesion to human skin, and water resistance.

[0117] [Moisture permeability] Moisture permeability is the rate at which water vapor passes through the patch (1 m 2 The mass was calculated per day. The moisture permeability was measured by measuring the mass (g) of water vapor passing through the test piece in 24 hours (1 day) when the relative humidity of the space separated by the patch was 90% in an atmosphere of 40°C and the space on the other side was kept dry with a moisture absorbent. 2 The moisture permeability was calculated by converting it to a value per unit. The moisture permeability was measured according to the moisture permeability test method (cup method) of moisture-proof packaging materials in JIS Z 0208:1976. Specifically, a circular patch with a diameter about 10 mm larger than the inner diameter of the cup was placed over a cup containing about 50 g of calcium chloride moisture absorbent, and then a rubber packing and a ring were placed over the patch and screwed in place to prevent it from slipping. Next, the total mass of the patch was measured, and it was then placed in a thermo-hygrostat under an atmosphere of 40°C and 90% RH, and the mass change was measured at regular intervals, and the moisture permeability was calculated according to the following formula. Moisture permeability (g / m 2 ·day)=W×240000 / S In the formula, S is the moisture permeability area (cm 2 ) and W represents the mass increase per hour (g / hr). The moisture permeability was evaluated according to the following criteria. A 2,500g / (m 2 1 day or more D 2,500g / (m 2 Less than 1 day

[0118] [Adhesion to human skin] The adhesive strength to human skin was measured according to the test method described in "10. Adhesive strength" of JIS Z 0237:2009, Test method for adhesive tapes and sheets. Specifically, the adhesive layer of a 15mm wide patch was applied to human skin in an atmosphere of 25°C, and pressed back and forth once at a speed of 300mm / min with a 2kg rubber roll. After leaving it for 20 minutes, the peel strength was measured at a peel angle of 90 degrees and a peel speed of 300mm / min. The human skin was degreased with isopropyl alcohol and air-dried before use. The adhesive strength to human skin was evaluated according to the following criteria. A 0.2~1.2N / 15mm D: Less than 0.2N / 15mm or more than 1.2N / 15mm

[0119] [water resistance] To evaluate water resistance, a 15 mm wide test piece of the adhesive layer of the patch was attached to a Bakelite plate, pressed with a 2 kg rubber roll at a speed of 300 mm / min, and left for 20 minutes.Then, the test piece was left in water for 20 minutes to check whether the adhesive layer had peeled off from the Bakelite plate. The water resistance was evaluated according to the following criteria. A: No peeling. D: Peeling.

[0120] (Production Example 1-1: Production of Compound P1) A slurry containing zinc hexacyanocobaltate-tert-butyl alcohol complex catalyst (hereinafter referred to as "TBA-DMC catalyst") and 30 g of 1-butanol as an initiator were charged into a pressure-resistant reaction vessel equipped with a stirrer and a nitrogen inlet tube to prepare a reaction liquid. The amount of the slurry charged was set so that the metal concentration of the TBA-DMC catalyst in the reaction liquid was 46 ppm. Next, after replacing the inside of the pressure-resistant reactor with nitrogen, the reaction solution was heated while stirring, and when it reached 135°C, heating was stopped, and while continuing stirring, 3970 g of propylene oxide (hereinafter also referred to as "PO") was supplied into the pressure-resistant reactor and reacted. Next, after confirming that the temperature rise of the reaction solution had stopped, the reaction solution was cooled to 135°C. After confirming that the internal pressure had stopped changing and the reaction had ended, the catalyst was neutralized and removed using a synthetic adsorbent (Kyowado 600S, manufactured by Kyowa Chemical Industry Co., Ltd.). The number of hydroxyl groups per molecule of the obtained compound P1, Mn (Mn of the polyoxyalkylene chain), and the proportion of ethylene oxide (hereinafter, also referred to as "EO") units are shown in Table 1 (hereinafter, the same applies).

[0121] (Production Example 1-2: Production of Compound P2) Compound P2 was produced in the same manner as in Production Example 1-1, except that 3758 g of PO and 970 g of EO were supplied instead of 3970 g of PO in Production Example 1-1.

[0122] (Production Example 1-3: Production of Compound P3) Compound P3 was produced in the same manner as in Production Example 1-1, except that the initiator was changed from 1-butanol to 38 g of glycerin, and 804 g of PO and 3217 g of EO were supplied instead of 3970 g of PO.

[0123] (Production Example 1-4: Production of Compound P4) Compound P4 was produced in the same manner as in Production Example 1-2, except that the initiator was changed from 1-butanol to propylene glycol.

[0124] In addition, commercially available compounds used were PREMINOL 7012 (hereinafter referred to as "compound P5"), PREMINOL S4011 (hereinafter referred to as "compound P6"), and PREMINOL S1004 (hereinafter referred to as "compound P7") manufactured by AGC Inc. The number of hydroxyl groups per molecule, Mn (Mn of polyoxyalkylene chain), and proportion of EO units of compounds P4 to P7 are shown in Table 1.

[0125] [Table 1]

[0126] (Production Example 2-1: Production of Monomer a1) In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 100 parts by mass of compound P1 obtained in Production Example 1-1, 1.39 parts by mass of 2-acryloyloxyethyl isocyanate (Kalends AOI, manufactured by Showa Denko KK, hereinafter also referred to as "AOI"), and 0.008 parts by mass of bismuth 2-ethylhexanoate (hereinafter referred to as "catalyst 1") were added and reacted at 70°C for 3 hours to obtain monomer a1. The ratio of NCO groups of 2-acryloyloxyethyl isocyanate to OH groups of monomer a1 (index (number of NCO groups / number of OH groups)), the ratio of EO units to monomer a1, and Mn are shown in Table 2 (hereinafter the same).

[0127] (Production Example 2-2: Production of Monomer a2) Monomer a2 was obtained in the same manner as in Production Example 2-1, except that 50 parts by mass of compound P1 and 50 parts by mass of compound P2 were used instead of 100 parts by mass of compound P1, and the amount of AOI used was 1.32 parts by mass.

[0128] (Production Example 2-3: Production of Monomer b1) In a reactor equipped with a thermometer, a stirrer and a cooling tube, 44 parts by mass of compound P5, 22 parts by mass of compound P6 and 34 parts by mass of compound P7 were added and mixed at 40°C, and then 6.78 parts by mass of diisocyanate (D201 (isocyanate group-terminated urethane prepolymer, manufactured by Asahi Kasei Corporation), hereinafter also referred to as "D201") and 0.02 parts by mass of dibutyltin dilaurate (hereinafter referred to as "catalyst 2") were added, and the reaction was started at 80°C. The isocyanate index was 90. Heat was generated by the reaction, the internal temperature became about 80°C, and the viscosity also increased over time. The mixture was reacted for 7 hours at 80°C while adding ethyl acetate to dilute it at appropriate times, and a monomer b1 having an average hydroxyl group number of 1.68 was obtained as a uniform transparent liquid. The average number fn of hydroxyl groups in the polymer b1 was calculated from the following formula (I). fn=Σ(fi×Wi / Mni) / Σ(Wi / Mni) ···(I) In the formula, fi represents the number of active hydrogen atoms per molecule of the initiator used as the raw material for each of the compounds P5, P6, and P7, Wi represents the mass part of each of the compounds P5, P6, and P7, and Mni represents the Mn in each of the oxyalkylene polymers.

[0129] (Production Example 2-4: Production of Monomer b2) In a reactor equipped with a thermometer, a stirrer and a cooling tube, 30 parts by mass of compound P3, 40 parts by mass of compound P4 and 30 parts by mass of compound P2 were added and mixed at 40°C, then 4.77 parts by mass of D201 and 0.02 parts by mass of dibutyltin dilaurate were added and the reaction was started at 80°C. The isocyanate index was 90. The reaction generated heat, the internal temperature reached about 80°C, and the viscosity also increased over time. The mixture was reacted for 7 hours at 80°C while diluting by adding ethyl acetate at appropriate times, and a monomer b2 having an average hydroxyl group number of 1.84 was obtained as a uniform transparent liquid. The average hydroxyl group number of monomer b2 was calculated in the same manner as that of monomer b1.

[0130] [Table 2]

[0131] [Example 1] As shown in Table 3, 100 parts by mass of monomer a1 and 0.3 parts by mass of a photoradical polymerization initiator (Irgacure 819, manufactured by BASF, hereinafter referred to as "photoinitiator 1") were mixed and degassed. The resulting preparation liquid was applied to a release-treated polyester film (release body, thickness 50 μm) as a peelable support using a knife coater so as to give a dry film thickness of 25 μm, and then coated with an HgXe lamp at an illumination intensity of 100 mW / cm. 2 , Accumulated light intensity 250mJ / m 2 The monomer a1 was pre-cured by irradiating it with light of 1000 nm. Then, the pre-cured product was coated with a 70 μm thick film having a moisture permeability of 6,580 g / (m 2 The nylon fabric was then layered on top of the polyester film, and irradiated with a HgXe lamp at an intensity of 100 mW / cm from the polyester film side. 2, cumulative light output 2,750mJ / m 2 The adhesive was cured by irradiating light of 1000 .mu.m to prepare a patch with a support. The moisture permeability, adhesive strength to human skin, and water resistance of the patch from which the support was removed were evaluated. The moisture permeability, adhesive strength to human skin, and water resistance of the obtained patch and adhesive layer, as well as the percentage of EO units in the adhesive layer, are shown in Table 3 (the same applies below). The moisture permeability of the pressure-sensitive adhesive layer is a calculated value obtained from the moisture permeability of the patch and the moisture permeability of the backing according to the following formula. (1 / Moisture permeability of adhesive layer)=(1 / Moisture permeability of patch)-(1 / Moisture permeability of support)

[0132] [Example 2] As shown in Table 3, a patch was prepared in the same manner as in Example 1, except that 50 parts by mass of monomer a1 and 50 parts by mass of monomer a2 were used instead of 100 parts by mass of monomer a1.

[0133] [Example 3] As shown in Table 3, 100 parts by mass of monomer b1 and 2 parts by mass of a curing agent (Coronate L, a Tosoh Corporation product name, hereinafter referred to as "curing agent 1") were uniformly mixed and then degassed. The mixture was then applied to a polyester film (release body, thickness 50 μm) that had been subjected to a release treatment as a peelable support using a knife coater so that the dry film thickness was 25 μm, and then the mixture was cured and dried at 120° C. for 3 minutes. Next, the cured product was applied to a support with a thickness of 70 μm and a moisture permeability of 6,580 g / (m 2 The nylon woven fabrics were layered together (100 mm x 100 mm) and then stored in a hot air dryer at 50°C for 3 days to complete the crosslinking reaction of the adhesive layer, thereby preparing a patch.

[0134] [Example 4] As shown in Table 3, a patch was prepared in the same manner as in Example 3, except that 100 parts by mass of monomer b2 was used instead of 100 parts by mass of monomer b1.

[0135] Examples 1 and 2 are working examples, and Examples 3 and 4 are comparative examples.

[0136] [Table 3]

[0137] The patches of Example 1 and Example 2 were rated "A" for both moisture permeability and water resistance, showing high moisture permeability regardless of the ethylene oxide content. The adhesive layer of Example 3 was rated "D" for moisture permeability, which was thought to be due to the low ethylene oxide content. The adhesive layer of Example 4 was rated "D" for water resistance, which was thought to be due to the high ethylene oxide content. [Explanation of symbols]

[0138] 1...adhesive material, 11...support, 12...adhesive layer, 13...carrier

Claims

1. Moisture permeability is 2,000g / (m 2 A support having a moisture permeability of 2,500 g / (m 2 A patch having an adhesive layer (a layer for one day or more), the pressure-sensitive adhesive layer comprises a polymer having a constituent unit based on a monomer having a (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain, the polyoxyalkylene chain having a number average molecular weight of 1,000 or more and an ethylene oxide unit content of 50 mass% or less, The monomer comprises a monomer a having one (meth)acryloyloxy group, a urethane bond, and a linear polyoxyalkylene chain in one molecule, and the proportion of the monomer a to the total mass of the monomers is 70 to 100% by mass.

2. The pressure-sensitive adhesive layer is located on at least a part of the surface of the support, and the moisture permeability of the area where the support and the pressure-sensitive adhesive layer overlap is 2,000 g / (m 2 2. The patch according to claim 1, wherein the duration of administration is 1 day or more.

3. The patch according to claim 1 or 2, wherein the thickness of the adhesive layer is 10 to 40 μm.

4. The patch according to any one of claims 1 to 3, wherein the support is a film, a porous film, a woven fabric or a nonwoven fabric, and the material of the support is at least one selected from an ether-based urethane resin, an ester-based urethane resin, a polyester resin, a polyamide resin and a polyolefin resin.

5. The patch according to any one of claims 1 to 4, further comprising a carrier provided in a peelable manner on the side of the pressure-sensitive adhesive layer opposite to the side on which the support is provided.

6. The patch according to any one of claims 1 to 5, which has an adhesive strength to human skin of 0.1 to 1.2 N / 15 mm.

7. The patch according to any one of claims 1 to 6, which is for medical use.

8. The patch according to claim 7, which is a dressing material.

9. The patch according to any one of claims 1 to 8, which is a patch to be applied directly to the skin.

Citation Information

Patent Citations

  • Repairing of on line hot rolling slab

    JP1979057446A

  • Pressure-sensitive adhesive sheet to be applied on skin

    JP2012051996A

  • Patch material

    WO2010137699A1